ANALISIS KUALITAS PUPUK KOMPOS DAUN KETAPANG DAN KOTORAN SAPI DENGAN PENAMBAHAN SUMBER KARBOHIDRAT BERBEDA - Wirnangsi Din Uno (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
Composting of organic waste into compost can be accelerated by using EM4. The nutrients can be obtained from carbohydrate sources, sugar cane, sugar, and brown sugar. This study aimed to determine the quality of Indian almond leaves compost with the addition of carbohydrate sources, sugar cane water, sugar, and brown sugar. The study employed a qualitative descriptive to describe the quality of the compost which refers to the National Compost Standard (SNI: 19-7030-2004). The results showed that the quality of the compost with the addition of the aforementioned carbohydrates sources has a C/N ratio value that exceeds the National Compost Standard (SNI: 19-7030-2004). Meanwhile, other characteristics such as temperature, pH, humidity, texture, color, and smell had met the requirements of the National Compost Standard (SNI: 19-7030-2004). The most effective source of carbohydrates for producing quality compost was brown sugar.